Microbiological quality assessment of raw salad vegetable sold in Minna metropolis, Nigeria (Journal of Bio-Science, 2018)
Vegetables are edible part of plants. A total of twenty five raw salad vegetables were collected and the microbiological assessment was made using pour plate method. The analysis was carried out on carrots, cucumber, cabbage, lettuce and tomatoes. The results obtained from this study revealed that the total heterotrophic viable bacterial counts, coliform counts and fungal counts for all the salad vegetables ranged from 1.4 × 106 - 6.2 × 106 cfu/g, 1.1 × 106 - 3.3 × 106 cfu/g and 2.1 × 103 - 4.5 × 105 cfu/g respectively. The data were subjected to One Way Analysis of Variance (ANOVA) test which showed that there was significant difference (p